2021
DOI: 10.1063/5.0037088
|View full text |Cite
|
Sign up to set email alerts
|

A Fock-operator complete active space self-consistent field (CAS-SCF) method combined with frozen-density embedding

Abstract: We report the implementation of a Fock-operator complete-active space self-consistent field (CAS-SCF) method combined with frozen-density embedding (FDE) into the KOALA quantum-chemistry program. The implementation is based on configuration interaction from an unrestricted reference determinant and is able to treat electronic configurations such as singlet, triplet, or quintet states embedded in a molecular environment. In order to account for possible spin polarization effects, the FDE contribution is extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Both ground and local (uncoupled) excited states have been addressed in recent work by Höfener and co‐workers employing methods such as Full CI and truncated CI schemes embedded in a DFT environment (or with an additional layer described by MP2), 334 or complete‐active‐space self‐consistent field (CASSCF‐)in‐DFT embedding 335 …”
Section: Extensions Of Subsystem Density‐functional Theory and Frozen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both ground and local (uncoupled) excited states have been addressed in recent work by Höfener and co‐workers employing methods such as Full CI and truncated CI schemes embedded in a DFT environment (or with an additional layer described by MP2), 334 or complete‐active‐space self‐consistent field (CASSCF‐)in‐DFT embedding 335 …”
Section: Extensions Of Subsystem Density‐functional Theory and Frozen...mentioning
confidence: 99%
“…Both ground and local (uncoupled) excited states have been addressed in recent work by Höfener and co-workers employing methods such as Full CI and truncated CI schemes embedded in a DFT environment (or with an additional layer described by MP2), 334 or complete-active-space self-consistent field (CASSCF-)in-DFT embedding. 335 An alternative class of easy-to-use, black-box wavefunction methods for excited states can be defined in terms of the algebraic diagrammatic construction (ADC) scheme for the polarization propagator. 336 A first-time combination of FDET with ADC of second order (ADC [2]) in 2016 showed that complexation-induced shifts in dispersion-or hydrogen-bonded systems can be reproduced with good accuracy.…”
Section: Excited Statesmentioning
confidence: 99%